Tracking P. infestans populations via molecular fingerprinting and a comprehensive isolate database - Cooke, David E. L; Lees, Alison K; Hansen, Jens Grønbech; Lassen, Poul; Andersson, Björn; Bakonyi, József (MTT, 2007)
Potato late blight control is challenging even in a stable environment. Understanding and, furthermore, predicting how the pathogen will respond to a given set of agronomic and environmental conditions is a key element of successful disease management. It is clear that blight control represents a moving target. Disease incidence and severity and the efficacy of control measures are not easy to predict and depend on several factors. Long and short-term changes in climatic conditions will clearly have a significant impact and chan-ges in active ingredients for chemical control, potato varieties and agronomic practices will similarly influence the disease. Overlying this are changes in the pathogen population that may either be occurring in response to, or independently from, the other factors. Fluxes in P. infestans populations have been described and there is an ever-expanding weight of literature documenting such change. However, until recently much of the population monitoring has been on a local scale and wider comparisons, over longer timescales, with meanngful sample sizes, have been challenging. The EU-funded EUCABLIGHT project has changed this via the assembly of a comprehensive database on almost 17,000 isolates of P. infestans from 21 European countries. A key element of the database is novel SSR fingerprint data that, for the first time, is allowing an objective picture of the pathogen population structure on a European scale. Overviews of the data and more detailed insights into local populations using SSR data will be presented and discussed.
Keywords: Ka; SSR; microsatellites; Eucablight